Police and people: role and responsibilities - Bharti, Dalbir (New Delhi, 2006)
This book brings home the point that the police and the people should develop mutual trust and join hands to fight crime and maintain public order for creating a safe, peaceful and harmonious atmosphere in the society.
Keywords: Police - India